In vitro lipolysis and physicochemical characterization of unconventional star anise oil towards the development of new lipid-based drug delivery systems. Issue 4 (April 2021) - Kamoun, Jannet; Krichen, Fatma; Koubaa, Imed; Zouari, Nacim; Bougatef, Ali; Abousalham, Abdelkarim; Aloulou, Ahmed
Abstract: Lipid-based drug delivery systems are widely used for enhancing the bioavailability of poorly water-soluble drugs. However, following oral intake, lipid excipients often undergo gastrointestinal lipolysis, which drastically affects drugs solubility and bioavailability. That's why developing new lipid excipients which are resistant to digestion would be of great interest. We studied here the potential role of the unconventional Chinese star anise whole seedpod oil (CSAO) as an alternative multifunctional lipid excipient. Pancreatic lipase-mediated digestion of the extracted crude oil emulsion was assessed in vitro . Pancreatic lipase, being a strict sn -1, 3-regioselective lipase, showed a high (16-fold) olive oil to CSAO activity ratio, which could be attributed to fatty acids composition and triglycerides intramolecular structure. For the sake of comparison, the non-regioselective lipase Novozyme® 435 exhibited higher activity than pancreatic lipase on CSAO emulsion, perhaps due to its ability to release fatty acids from the internal sn -2 position of TAGs. Apart counteracting lipolysis, CSAO oil also showed additional biopharmaceutical benefits including moderate antioxidant and antihypertensive activities. Altogether, these findings highlight for the first time the potential use of star anise unconventional whole seedpod oil as a multifunctional lipid excipient for the development of new lipid formulations. Abstract : In vitro lipolysis; Star anise seedpod oil; Lipid-based drug delivery systems; Multifunctional lipid excipient; Biological activities.